Sacroiliitis and sacral insufficiency fracture: A rare coexistence - Vural, Meltem (Turk J Phys Med Rehabil, 2018)
Sacral insufficiency fracture (SIF) is an uncommon cause of hip and back pain. Sacroiliitis, often a feature of inflammatory conditions of spinal column, is inflammation of sacroiliac joints. Herein, we report a 41-year-old woman presenting with a SIF and sacroiliitis as a part of non-radiographic axial spondyloarthritis.